Additive metallization of alumina with copper-titanium powder blends for power electronic applications - Hecht, Christoph; Häußler, Felix; Schadow, Eric; Stoll, Thomas; Sprenger, Mario; Franke, Jörg (Advancing Microelectronics, 2023)
Additive manufacturing shows great potential to further increase the performance of power electronic modules through novel packaging concepts. Such an approach is the integrated manufacturing of metal-ceramic substrates by means of laser powder bed fusion of metals (PBF-LB/M). With this layered additive manufacturing process, planar ceramic substrates can be metallized and electrically functionalized for power electronic applications. In this paper Al2O3 ceramic substrates are metallized via PBF-LB/M by selectively melting applied powder layers with software defined geometries. The investigated powders are mixtures of copper and titanium powders with 1 wt.%, 5 wt.% and 10 wt.% titanium in order to enable bonding by creating a titanium-oxide reaction layer at the interface to the ceramic. Shear tests and microstructural investigations show that a subsequent heat treatment increases the adhesion and density of the metallization. By energy dispersive X-ray microscopy (EDX) the partial formation of reaction layers is detected.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Active Metal Brazing; Laser powder bed fusion; Power electronics; Substrates

Additive Metallization of Alumina with Copper-Titanium Powder Blends for Power Electronic Applications - Hecht, Christoph; Schadow, Eric; Sprenger, Mario; Häußler, Felix; Stoll, Thomas; Franke, Jörg (IMAPSource Proceedings 2023 (EMPC), 2023)
Additive manufacturing shows great potential to further increase the performance of power electronic modules through novel packaging concepts. Such an approach is the integrated manufacturing of metal-ceramic substrates by means of laser powder bed fusion of metals (PBF-LB/M). With this layered additive manufacturing process, planar ceramic substrates can be metallized and electrically functionalized for power electronic applications. In this paper Al2O3 ceramic substrates are metallized via PBF-LB/M by selectively melting applied powder layers with software defined geometries. The investigated powders are mixtures of copper and titanium powders with 1 wt.%, 5 wt.% and 10 wt.% titanium in order to enable bonding by creating a titanium-oxide reaction layer at the interface to the ceramic. Shear tests and microstructural investigations show that a subsequent heat treatment increases the adhesion and density of the metallization. By energy dispersive X-ray microscopy (EDX) the partial formation of reaction layers is detecte
Keywords: Substrates; Laser powder bed fusion; Power electronics; Active Metal Brazing